Factors associated with alcohol consumption in adolescents in the north of Brazil (Revista Contexto & Saúde, 2023)
The aim of this study was to identify the prevalence and factors associated with alcohol consumption. Cross-sectional study with 3620 adolescents from public and private schools in Porto Velho (RO), 2018. Poisson regression was performed to calculate the prevalence ratios. The prevalence of alcohol consumption was 22.2%, and the alcoholic beverage with the highest preference to beat (cachaça+vodka/cognac) 37.1%. They start consuming alcohol around 12 years. Higher alcohol consumption was associated with male risk factors (p=0.009), 14 years or more (p
Keywords: Adolescent. Alcohol. Risk factors.